Major and Trace Elements Geochemistry of Dong Ho Sediments (Quang Ninh, Viet Nam): Imlication for Paleoenvironmental Condition - Vuong, Nguyen Van; Hoai, Luong Thi Thu (VNU Journal of Science: Earth and Environmental Sciences, 2018)
The Dong Ho sedimentary formation consists of gravel, sand and sandstone, mudstone interbeded with asphalt layer or oil shale cropping out at Quang Ninh is considered as outcrop of petroleum potential source rock and correlated to source rock of the Cenozoic basins on the continental shelf of Southeast Asia. Geochemical investigation of major and trace elements content variation from 13 typical samples selected from diferent layers leads to divide the Dong Ho formation into two parts: the lower part characterized by unclear variation while the upper part exposing a more clear trend. The paleoenvironmental proxy and the CIA, CIW, PIA and CPA indices of the Dong Ho formation revealed high weathering intensity. V/Ni and C/Cr s vary from 0.14 to 1.52; and from 0.02 to 0.52 respectively indicate to oxic depositional environment. The provenance of the Dong Ho sedimentary layers come from the recycling of sedimentary source rocks and deposited within freshwater lacustrine environment dominated by humid climate with estimated mean annual rainfall of 1533 mm/yr±181 mm before changing to wet and reduction environment during diagenesis. Keywords: Major element, trace element, geochemistry, Dong Ho, paleoenvironment.